NEW RECORD OF THE AMBROSIA BEETLE, Treptoplatypus micrurus Schedl. ATTACK ON SONOKEMBANG (Pterocarpus indicus Willd.) IN BATU, INDONESIA - Tarno, Hagus; Suprapto, Hasan; Himawan, Toto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Sonokembang (Pterocarpus indicus Willd.) is commonly planted as an ornamental tree in Batu city, East Java. In 2012 and 2013, there were some dying trees of sonokembang along the road of Batu city, and there were some indications that the signs and symptoms might be related to the ambrosia beetle samples from Batu. To clarify the precise condition, identification of beetle samples was needed in this research. Based on survey and sample collections conducted in Batu from the early July 2013 to the end of March 2014, characteristic of damage on trees was observed together with the presence of beetle collected. Identification was based on morphological characters such as posterior elytral declivities and body size of male, and mycangia on female`s pronotum. Based on the morphological characters, there were some special characters which described such as 1) the body size of female adult was bigger than male adult, 2) elytral declivities on male adult was unique, and 3) there was mycangia on pronotum of female adults. Morphological char-acters showed that the ambrosia beetle attacked on sonokembang belonged to Treptoplatypus mi-crurus Schedl. This ambrosia beetle species seems to be the responsible agent that caused dying trees of sonokembang.